Ecological Literacy, Environmental Awareness, Academic Ability and Environmental Problem-Solving Skill at Adiwiyata School - Lenny Prastiwi; Diana Vivanti Sigit; Rizhal Hendi Ristanto (Indonesian Journal of Science and Education (IJOSE), 2019)
This study aimed to analyze ecological literacy, environmental awareness, academic ability, and environmental problem-solving skill at the Adiwiyata schools in Tangerang City. The research method used descriptive quantitative with survey technique. The respondents consisted of 245 students of class XI Science from three Adiwiyata Senior High Schools in Tangerang City. The instruments used in this study were tests and questionnaires. Ecological literacy was measured using multiple choice tests and questionnaires, environmental awareness was measured using a questionnaire, academic ability was measured by using the total national exam scores of students when in Junior High School, and environmental problem-solving skill was measured using essay tests. The results showed that the majority of students had ecological literacy scores with basic categories, environmental awareness scores with very good categories, academic ability scores with moderate categories, and scores for environmental problem-solving skill with enough categories. Based on the results of the study, other schools are expected to also be able to implement the Adiwiyata program so that students can develop ecological literacy, environmental awareness, academic ability and environmental problem solving skills. Keywords: Academic Ability, Ecological Literacy, Environmental Awareness, Problem-Solving Skills.